The valuation of closed-end investment companies - Goh, Hwee Jack (2015)
This paper examines the proposition that fluctuations in discounts of closed-end funds in Singapore are driven by changes in management fees . The agency cost theory implies that higher management fees lead to higher discounts and that fluctuations in management fees causes discounts to fluctuate. The evidence partially supports these predictions. Based on our findings, we conclude that there is convincing support for the hypothesis that higher management fees lead to closed-end fund share prices in Singapore being traded at a discount to their net asset value (NAV) . On the other hand, only weak support was shown to support the premise that fluctuations in management fees and fluctuations in discounts are positively correlated.